Regional Economic Literature Analysis: The Effect of PPPK Civil Servant Status Changes to PNS on Local Economic Circulation in Jambi Province - Pardinal; Mayasari, Mike; Puji Lastari, Pratiwi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to comprehensively examine the regional economic effects of the employment status change from Government Employees with Work Agreements (PPPK) to Civil Servants (PNS) in Jambi Province. Using a literature analysis approach, this research explores previous studies that discuss the relationship between civil service employment policies and regional economic dynamics. The main focus is directed toward the impact of increased income and job stability on money circulation, household consumption, savings, and the growth of the MSME sector. The synthesis results indicate that the transition from PPPK to PNS has the potential to create an economic multiplier effect through increased purchasing power, government employee spending, and local investment. On the other hand, fiscal policy and public expenditure planning become determining factors to ensure that these economic benefits remain sustainable. This article contributes theoretically to strengthening the model of regional economic analysis based on public employment policy and provides policy recommendations for optimizing apparatus-based regional development